Enhancing Corporate Environmental Performance Through Reporting and Roadmaps. (24th September 2013) - Caritte, Victor; Acha, Salvador; Shah, Nilay
Abstract Managing the carbon footprint of companies and addressing their respective decarbonization plans is a challenging endeavour. The aim of this study is to help companies better understand the issues around decarbonization and environmental performance by suggesting a holistic management process on which they could embark. This process comprises two crucial steps, which are (a) sustainability reporting and (b) low‐carbon roadmaps. These steps are covered and further developed based on a detailed study of the UK food retail sector. This sector is relevant due to its economic and environmental importance, but most importantly it has a significant record of available environmental reports in the public domain and a large potential to influence consumers, policy makers and multiple supply chains. Sustainability reporting is assessed by analysing environmental KPIs disclosed in corporate social responsibility (CSR) reports, and then these are compared against industry standards. This analysis highlights a general lack of consistency and transparency in CSR reporting of UK food retailers. Consequently, a low‐carbon roadmap based on relevant KPIs and on the 'backcasting' framework is presented as a case study in order to showcase how a hypothetical UK food retailer can employ a low‐carbon roadmap. The case study demonstrates that ambitious environmental targets are achievable if robust corporate action plans are followed. Furthermore, the case study indicates that capital might be misallocated in favour of highly visible environmental stores and on‐site energy generation technologies, whilst more could be done by applying energy efficiency measures that have the potential to deliver substantial carbon savings. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.